2014
DOI: 10.1007/s12639-014-0431-9
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical assessment of oxidative status versus liver enzymes in patients with chronic fascioliasis

Abstract: The aim of this study was to examine the oxidative status in Egyptian patients suffering chronic fascioliasis. The relationship between serum malondialdehyde (MDA) levels, superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPX) activities was investigated in relation to the level of liver enzymes; ALT and AST compared to healthy controls. Twenty patients versus ten controls were included in the study. Among cases the MDA, CAT, AST and ALT were higher than controls, while SOD and GPX higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…Lipid peroxidation was identified by increased seric and hepatic MDA levels of infected animals, which reflected the severity of cellular damage. Lipid peroxidation in cattle infected by F. hepatica enhanced the oxidation of polyunsaturated fatty acids and caused lipid peroxidation, as reported by Kamel et al (2015) in humans. The increase of MDA and ROS levels occurred at similar periods in this experiment.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Lipid peroxidation was identified by increased seric and hepatic MDA levels of infected animals, which reflected the severity of cellular damage. Lipid peroxidation in cattle infected by F. hepatica enhanced the oxidation of polyunsaturated fatty acids and caused lipid peroxidation, as reported by Kamel et al (2015) in humans. The increase of MDA and ROS levels occurred at similar periods in this experiment.…”
Section: Discussionsupporting
confidence: 61%
“…Therefore, its suppression leads to H 2 O 2 accumulation up to toxic levels, as observed by Kamel et al . (2015) in hepatic tissue of patients with chronic fasciolosis. However, in this study increased hepatic GPx activity was observed in infected animals by F. hepatica, probably due to compensatory mechanisms for reduced CAT activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the people chronically infected by Fasciola are asymptomatic but they are not necessarily free of inflammation [ 7 ]. There is a degree of inflammation into the liver in those chronically infected individuals by means of an increase in serum lipid peroxidation and a decrease in antioxidant enzymes, but the period between initial infection and developing of liver fibrosis in humans is still unknown [ 40 ]. Intensity of infection, length of infection, re-infections, other liver diseases, alcohol consumption, co-infection with chronic viral hepatitis, among others; are factors to be considered when assessing liver disease in infected individuals by Fasciola in endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…Many biologists reported that ALT and AST activities increased among patients who had acute Fasciola infection. 24 , 25 The higher value of ALT and AST is due to the stage of extensive destruction of the hepatic parenchyma which linked with some degree of hepatic necrosis that occurs during migration of immature worms. 26 Parenchymal damage in human fascioliasis occurs due to the activity of AST.…”
Section: Discussionmentioning
confidence: 99%